Cutaneous sensibility impairmentafter mandibular sagittal split osteotomy: a prospective clinical study of the spontaneous recovery - Monnazzi, Marcelo Silva; Gabrielli, Mário Francisco Real [UNESP]; Passeri, Luis Augusto; Gabrielli, Marisa Aparecida Cabrini [UNESP] (Elsevier, 2012)
Purpose The aim of this prospective study was to objectively evaluate the inferior alveolar nerve (IAN) sensory disturbances in patients who underwent sagittal split ramus osteotomy (SSRO) and its spontaneous recovery and to define the incidence of sensibility loss, time, and area at which the recovery occurs. Patients and Methods Clinical evaluation of the IAN sensory disturbance was undertaken preoperatively and at the first week, fourth week, 2 months, and 6 months postoperatively in 30 patients who underwent SSRO at the Oral and Maxillofacial Surgery Division of the Araraquara Dental School--Unesp and at the Plastic Surgery Division of the Medical Sciences School--Unicamp. The 30 patients were examined at all periods regarding the IAN functionality by Semmes-Weinstein testing. Results The mean age of the patients included in this study was 29.36 years old. All patients showed sensibility loss at the 7-day evaluation time. The comparison between sides, gender, and age did not show any significant difference. In most of the examined zone, the data collected at 6 months were statistically similar to the data collected at the preoperative period. All zones presented significant recovery, starting from 30 days after surgery. Twenty patients had total spontaneous recovery at the final period, in all examined zones. Conclusions The SSRO presents the disadvantage of temporary paresthesia; however, spontaneous nerve function recovery does occur. The Semmes-Weinstein test is a reliable, inexpensive, and easy-to-apply tool, which can be used for clinical evaluation on a daily basis at offices and hospitals.